Factibility of treat wineyard wastewater through anaerobic biodigestion with a from cow”™s waste - Del Real Olvera, J.; Prieto García, F.; Santos López, E.; Román Gutiérrez, A.; Gordillo Martínez, A. (Rev. Téc. Fac. Ing. Univ. Zulia)
The anaerobic digestive process is a natural biological process in which an interlaced part of community of bacteria cooperates to obtain stable and auto-regulated fermentation, transforming the residual organic matter into biogas. Four main groups of bacteria coexist in the process, being the most important the methanogenics, one which has their natural origin in the stomach of the rumiants. The aim of this study was to take a microbial from cow to treat a wine distillery wastewater to search whiter degradation of organic matter expressed like COD and generation of biogas. The results demonstrated capacity of degradation of the substrate, de creasing more than half the initial organic content (56,7 Ó 0,8%). On the other hand, the volume of biogas generated by the system at first hours of reaction, were crucial on biodigestion process. Finally, the ratio between biogas and COD indicated that 971,2 Ó 1,4 mL of biogas was generated per each gram of COD, which such removal a mean an accept able biodegradation of the wineyard waste.